Participant and Staff Experiences in a Peer-Delivered HIV Intervention with Injection Drug Users. (February 2014) - Kostick, Kristin M.; Weeks, Margaret; Mosher, Heather
We explore ethical issues faced by investigators as they conduct research as part of a peer-delivered HIV/AIDS risk reduction program for injection drug users (IDUs). Staff and participant experiences in peer-delivered interventions among IDUs have come under scrutiny by ethics researchers because of their potential to inadvertently and negatively impact participant rehabilitation due to continued engagement with drug-using networks during the course of outreach. This study explores whether enhanced communication of participant concerns and experiences with clinic and research staff helps to reduce inadvertent malfeasance in peer-delivered drug treatment interventions. Results contribute to the development of patient support infrastructure in peer-delivered risk reduction programs involving IDUs.